2016
DOI: 10.1016/j.jcat.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

The use of bimetallics to control the selectivity for the upgrading of lignin-derived oxygenates: Reaction of anisole on Pt and PtZn catalysts

Abstract: a b s t r a c tThe adsorption and reaction of anisole on Pt and PtZn catalysts were investigated using both model single crystal and high surface area supported metal catalysts. Temperature programmed desorption (TPD) and high resolution electron energy loss spectroscopy (HREELS) studies of the interaction of anisole with Pt (1 1 1) demonstrated that there is a strong interaction between the phenyl ring of anisole and the surface, resulting in CAO and CAH bond scission at relatively low temperatures. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 48 publications
8
50
0
Order By: Relevance
“…Benzene was observed in a broad peak between 300-550 K, with the peak center near 430 K. Other than benzene, the only reaction products detected were CO and H 2 . The H 2 was produced in two distinct peaks centered at 360 and 490 K, with a much broader feature spanning from 540-750 K. CO desorbed in two peaks centered at 430 and 490 K. With the exception that benzene was observed, these data are in agreement with that reported in our previous study [17]. These results are also similar to those reported previously by Réocreux et al [25] who also observed benzene as a product, although they reported only a single CO peak centered at 440 K. This difference may be related to the different anisole doses used in the two studies.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Benzene was observed in a broad peak between 300-550 K, with the peak center near 430 K. Other than benzene, the only reaction products detected were CO and H 2 . The H 2 was produced in two distinct peaks centered at 360 and 490 K, with a much broader feature spanning from 540-750 K. CO desorbed in two peaks centered at 430 and 490 K. With the exception that benzene was observed, these data are in agreement with that reported in our previous study [17]. These results are also similar to those reported previously by Réocreux et al [25] who also observed benzene as a product, although they reported only a single CO peak centered at 440 K. This difference may be related to the different anisole doses used in the two studies.…”
Section: Resultssupporting
confidence: 92%
“…We postulate that this change in bonding configuration is a result of the oxygen in the carbonyl group interacting with an oxyphilic Co adatom on the Pt(111) surface as shown in figure 6. This conclusion is consistent with what we have observed previously for Pt(111) surfaces modified with oxyphilic Zn adatoms [17,31] where the oxygens in both alcohols and carbonyl compounds preferentially bond to the Zn sites on these surfaces.…”
Section: Anisole Reaction On Co/pt(111)supporting
confidence: 93%
See 3 more Smart Citations